The Role of Price to Earning Ratio as an Intervening Variable in the Relationship Between Financial Ratios and Stock Returns of Transportation Sector Issuers on the Indonesia Stock Exchange During the 2020–2024 Period - Boquifai, Petronela Maria Merces da Costa; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Sean Institute, 2025)
This study investigates the role of the Price to Earning Ratio (PER) as a mediating variable in the relationship between financial ratios, Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER. and stock returns of transportation companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Employing a quantitative approach with Structural Equation Modeling (SEM) using SmartPLS, the analysis reveals that CR and DER significantly influence PER, while ROA does not. However, PER does not significantly affect stock returns, indicating it is not an effective mediating variable. Additionally, the direct effects of ROA, CR, and DER on stock returns are also statistically insignificant. These findings suggest that stock returns in the transportation sector are more influenced by external factors, such as macroeconomic conditions and investor sentiment, than by internal financial metrics. The study contributes to the financial literature by emphasizing the limited role of traditional financial ratios in predicting stock performance within this sector.